New Insights into Structure–Activity Relationship of Ipomoeassin F from Its Bioisosteric 5-Oxa/Aza Analogues - Zong, Guanghui (Eur J Med Chem, 2017)
Ipomoeassin F, a plant-derived macrolide, exhibited single-digit nanomolar growth inhibition activity against many cancer cell lines. In this report, a series of 5-oxa/aza analogues was prepared and screened for cytotoxicity. Replacement of 5-CH(2) with O/NH simplified the synthesis and led to only a small activity loss. N-methylation almost completely restored the potency. Further studies with additional 5-oxa analogues suggested, for the first time, that size and flexibility of the ring also significantly influence the bioactivity of ipomoeassin F.